Dramatizing Deirdre - Bastos, Beatriz Kopschitz Xavier (ABEI Journal, 2011)
The alarming cry that characterizes the myth of Deirdre breaks time, genre and geographical boundaries. Originally oral, then written narrative, the story was splendidly dramatized in the Irish Revival, in the well-known plays by William Butler Yeats, Deirdre (1907), and John Millington Synge, Deirdre of the Sorrows (1909). Less known Revival dramatizations of the myth include George Russell’s Deirdre (1902) and Eva Gore Booth’s The Buried Life of Deirdre (1908-12). Much later, the myth was revisited by Donagh MacDonagh in Lady Spider – A Play about Deirdre (1951), by Ulick O’Connor in Deirdre (1977), and by Mary Elizabeth Burke Kennedy, as part of the play Women in Arms (1984). The most recent dramatized version of the myth is Vincent Woods’ A Cry from Heaven (2005). The aim of this article is to comment on thetransformations that the story has suffered in dramatic form in the twentieth and early twenty-first centuries, somehow responding to historical and social changes in Ireland.